Similar and different between Arabic and Arabian peninsula Accents balance linguistic Study Voice of the Sein typically (Journal of the College of Education for Women, 2019)
Languages were not found in our life in a way utter coincidence , and it’s not flounce on people’s tongue randomly ‚ but laws are the controlling in languages‚ these laws could be lift to the same level of natural laws‚ phonetics form the main part in producing those languages‚ the Arabic language is one of those languages ‚ it’s largest dialects in Arabian Peninsula according to speakers number ‚ Arabic language link with these dialects through properties and phenomena sound and grammar‚ from this point my topic search is came Similar and different between Arabic and Arabian peninsula Accents balance linguistic–study voice of the Seine typically ) . and Similar and different of the phenomena of the Arabic language and similar speaking of the two votes in one word each of which is characterized as different from the other‚ as manifest and whisper or the dishes and opening up would receive as result of that weight in the pronunciation resorts speaker to lie between the two sounds by replacing one of them to another voice to reduce‚ the effort muscular effort when the two sound pronoun citation‚ as well as an investigation in to the voice of harming between them it is similar appearances substitution and slurring the succession they on the contrary similar they are converting a two sound identical to another voice sound these phenomena are common phenomena in the Arabian peninsula accents as these dialects and is knew as but they dispersed after that , then came this research to pave and three axes and a conclusion, boot talked about similar offense in general , the first axis: the substitution, touched it to the substitution language and idiomatically, and the types of substitution, and cannibalization between the Seine and other voices in the Arab Arabian Peninsula and dialects, Axis ll : slurring and talked in it for slurring language and idiomatically, and sections slurring, and slurring voice between the Seine and the only sounds with the examples mentioned, the third axis: the offense, has been defined by this phenomenon and departments with examples of violation of Seine between the voice and other sound in Arabic and dialects of the Arabian Peninsula.